Pencegahan Cedera Olahraga Melalui Pemanasan Dan Pendingingan Yang Tepat Pada Atlet BA Pakuan Karawang - Gunawan, Gunawan; Balqis, Virgie Naila; Putra Gusman, Sheva Ahmad Dzakiawan; Hidayat, Mochammad Ariel Fikri; Rahayu, Selvia; Setiawan, Muhammad Arief (Jurnal MensSana, 2025)
Sports injuries are a common problem experienced by athletes due to a lack of proper warm-up and cool-down practices before and after exercise. Warming up increases body temperature, muscle flexibility, and nervous system readiness, while cooling down helps gradually lower heart rate and reduce lactic acid buildup. Both play a crucial role in maintaining physical fitness and preventing injury during sports activities. Based on this background, this study was conducted to determine the effectiveness of proper warm-up and cool-down practices in preventing sports injuries in BA Pakuan Karawang athletes. This study used a qualitative method with a one-group pretest-posttest design, involving 20 female volleyball athletes as a sample. Data were obtained through questionnaires administered before and after the four-week training program. Descriptive analysis was conducted to examine changes in behavior and injury complaints before and after the intervention. The results showed a 19.8% increase in positive athlete behavior and a 42.8% decrease in injury complaints after the implementation of a structured warm-up and cool-down. These findings indicate that both training stages significantly influence injury prevention and increase athletes' physical fitness. These results align with previous research confirming that consistent warm-up and cool-down practices can improve neuromuscular performance and accelerate recovery after exercise. Thus, coaches and sports institutions are advised to make warm-ups and cool-downs a routine part of every training session to minimize the risk of injury and support optimal athlete performance.